Digital Transformation Strategy to Optimize Company Performance - Hendra Halim; T. Meldi Kesuma; M. Ridha Siregar (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research explores digital transformation strategies to enhance company performance, identifying four common types of strategies emerging through the utilization of technologies such as artificial intelligence, data analytics, cloud computing, and the Internet of Things. Mature digital transformation strategies are key to success, focusing on specific goals and aspects. Research results indicate that companies with clear and comprehensive digital strategies tend to be more mature and achieve better performance. Digital transformation also impacts customer experience, facilitates better decision-making through data and analytics, and aligns human resources with digital technology. In conclusion, digital transformation is not just about technology; it involves digitizing all aspects of business to provide the best possible customer experience.